ePoster 2019
DOI: 10.1136/ijgc-2019-esgo.717
|View full text |Cite
|
Sign up to set email alerts
|

EP663 Correlation between adenomyosis and endometrial cancer: 6-year experience of a single center

Abstract: Introduction Adenomyosis often co-exists in the pathological specimens after surgery for endometrial cancer. The aim of this study is to describe the clinicopathological and oncological characteristics of these patients and further investigate the possibility of malignant transformation in the adenomyotic tissue. Methods We retrospectively reviewed the medical records of all patients that underwent hysterectomy for endometrial cancer (January 2012 – December 2017). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Among these 64 patients, 7 (11%) had a malignant transformation of adenomyosis. 30 In our study, endometrial carcinoma was found in 0.8% of patients with diffuse adenomyosis and all cases were early-stage, lowgrade hormone sensitive tumors. However, the number of our cases was relatively insufficient to make a general statement.…”
Section: Discussionsupporting
confidence: 45%
“…Among these 64 patients, 7 (11%) had a malignant transformation of adenomyosis. 30 In our study, endometrial carcinoma was found in 0.8% of patients with diffuse adenomyosis and all cases were early-stage, lowgrade hormone sensitive tumors. However, the number of our cases was relatively insufficient to make a general statement.…”
Section: Discussionsupporting
confidence: 45%
“…13 articles remained after abstracts screening, and were assessed for eligibility. Finally, eight studies were included in the qualitative and quantitative analyses [6][7][8][9][10][11][12][13] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have assessed the histological co-existence of endometrial carcinoma (EC) and adenomyosis reporting different data [6][7][8][9][10][11][12][13]. The two pathologies share common etiopathogenetic mechanisms including unopposed hyper-oestrogenic state, inflammatory milieu and molecular features favoring cell proliferation and inflammation [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, adenomyosis coexisted with endometrial cancer in 0-70% 14 of cases, which is consistent with the studies we included 6.4-66% of cases. 4,[8][9][10][11][12][15][16][17][18][21][22][23][24] Furthermore, a population-based study comprising 768 patients with adenomyosis alone exhibited a fivefold increased risk of developing endometrial cancer. 25 Despite the common context, the mechanism of action of adenomyosis in endometrial cancer remains elusive.…”
Section: Discussionmentioning
confidence: 99%